ANALISIS PERBANDINGAN KINERJA PORTOFOLIO SAHAM DENGAN METODE SHARPE, TREYNOR DAN JENSEN (Studi Kasus Indeks LQ 45 Di Bursa Efek Indonesia Periode 2008 – 2012) - Edy Arisonda (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
ABSTRACT This research focuses on portfolio performance analysisof LQ 45that used method Sharpe, Treynor and Jensen. Inorder to reveal the presence or absence of differences on method of performance measurement, Nonparametric techniques is used, Kruskal - Wallish. Results of testing with the Kruskal Wallish of the three methods showsthat χ2 = 4.231 , with a significance of 0.121 . It is proved that the probability of testing > 0.05 and χ2 count < χ2 table (5, 99). These results indicate that no significant difference between the tehcniques tes. Furthermore, according the three tools used, Treynor’s shows the consistent result from perfomance measurement. Keywords : Sharpe Index, Treynor, and Jensen portfolio performance LQ 45.